Acupressure dan Senam Kaki terhadap Tingkat Peripheral Arterial Disease pada Klien DM Tipe 2 - Linda Widiastuti (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effect of acupressure intervention, foot gymnastics, and acupressure combination with foot gymnastics on the level of PAD in type 2 DM clients. The results showed that there was a significant relationship between age (p = 0,000), smoking history (p = 0,000), and duration of DM (p = 0.028) with the level of PAD. Paired difference test results found that there were significant differences in the level of PAD before and after the intervention in the acupressure group (p = 0,000), foot gymnastics (p = 0,000), and the combination of acupressure with foot gymnastics (p = 0,000). The results of the ordinal logistic regression test showed that the combination of acupressure with foot exercises gave the strongest influence on the level of PAD (p = 0,000) with a contribution of 36.4%, acupressure (p = 0.005) with a contribution of 30.2%, and foot exercises ( p = 0.033) with a contribution of 20.6%. Conclusions, acupressure, and foot exercises affect the level of PAD of type 2 DM clients. Keywords: Acupressure, DM type 2, Peripheral Arterial Disease, Foot Gymnastics